Influence Chair Yoga Exercise on Decreasing the Risk of Falls for the Elderly - Novistianasari, Florida; Halimah, Nurul; Mufarokha, Hanim; Fariz, Achmad (Newinera Publisher, 2025)
Falls are a significant concern among the elderly, often leading to injury, disability, and reduced quality of life. This study aims to examine the influence of chair yoga exercises on reducing the risk of falls among residents at St. Joseph's Nursing Home, Kediri. Using a pre-experimental one-group pretest-posttest design, this research assessed fall risk levels before and after a structured chair yoga intervention. The study employed the Timed Up and Go Test (TUGT) to measure fall risk, with data analyzed using paired t-tests to determine the effectiveness of the intervention. The results demonstrated a significant decrease in fall risk scores following the chair yoga program, highlighting its efficacy in enhancing balance and physical stability among participants. The findings suggest that incorporating chair yoga into daily routines can serve as a practical and accessible strategy for fall prevention in elderly populations. This study contributes to the growing body of evidence supporting yoga-based interventions as a non-pharmacological approach to improving the health and well-being of older adults in nursing care settings.